Microfluidic liquid sheets as large-area targets for high repetition XFELs - Hoffman, David J.; Van Driel, Tim B.; Kroll, Thomas; Crissman, Christopher J.; Ryland, Elizabeth S.; Nelson, Kacie J.; Cordones, Amy A.; Koralek, Jake D.; DePonte, Daniel P. (Frontiers in Molecular Biosciences, 2022)
The high intensity of X-ray free electron lasers (XFELs) can damage solution-phase samples on every scale, ranging from the molecular or electronic structure of a sample to the macroscopic structure of a liquid microjet. By using a large surface area liquid sheet microjet as a sample target instead of a standard cylindrical microjet, the incident X-ray spot size can be increased such that the incident intensity falls below the damage threshold. This capability is becoming particularly important for high repetition rate XFELs, where destroying a target with each pulse would require prohibitively large volumes of sample. We present here a study of microfluidic liquid sheet dimensions as a function of liquid flow rate. Sheet lengths, widths and thickness gradients are shown for three styles of nozzles fabricated from isotropically etched glass. In-vacuum operation and sample recirculation using these nozzles is demonstrated. The effects of intense XFEL pulses on the structure of a liquid sheet are also briefly examined.